The Hydrolysis of Ear-Mushroom Cultivation Media Residue by Using Three Kinds of Cellulase Enzymes - Denny Irawati (Jurnal Ilmu Kehutanan)
Ear mushrooms (Auricularia polytricha) belongs to class Basidiomycetes is widely cultivated in Indonesia. After 6-8 months of cultivation, the media should be renewed. Therefore, the rest of the media is under utilized and just thrown away as a waste. This is dangerous because the residual mycelia that contained in the rest of the media may further degrade the media. This pollutes the environmental pollution due to discharge of methane into the air. Therefore, the utilization of residual ear mushroom media needs to be processed. In fact, this residue can produce a reducing-sugar using various commercial cellulase enzymes. This study used the residual media of the cultivation of mushroom derived from three types of wood, i.e. sengon (Falcataria moluccana), teak (Tectona grandis), and meranti (Shorea sp.), and then they were hydrolyzed using three types of cellulase enzymes, i.e. Driselase, Cellulase “Onozuka” R-10, and Meicelase. The hydrolysis rate was measured and the reducing-sugar yield was analyzed. The design used was completely randomized design with 3 x 3 factors and 3 replications for each treatment. The results showed that the residue of the mushroom cultivation media has the potential of reducing sugar as a raw material which can then be fermented into bio-ethanol or other chemicals. Hydrolysis rate ranged from 1.43 to 21.29%. The highest combination of residual cultivation medium was made from meranti sawdust by using Meicelase enzyme. The highest reducing sugar content yield were also resulted from the combination of the same treatment, which amounted to 127.7 mg/g or 12.8% with output range between 56.0 and 127.7 mg/g (or yield 5.6-12.8%).